2018
DOI: 10.5897/ijbc2017.1159
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous knowledge based identification of medicinal plants in Central Zone of Tigray, North Ethiopia

Abstract: There are many traditional medicine practitioners in every corner of the world, which can be grouped into spiritual healers and herbalists. Both groups do not tell to others about medicinal plants sometimes even to their descendants. This may have many different reasons, some say the medicine becomes functional if it is used in secret and some do not tell others fearing for competition of market as well as the medicinal plants because their abundance is mostly limited due to over exploitation. This study was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In the central zone of Tigray, Gebrekidan et al (2012) also indicated that the proportion of male household heads was higher than that of female heads. This indicates that females are less dependent on urban dairy production than males, so attention must be given to the females participation in smallholder dairy farming for work, employment, and income generation.…”
Section: Socio-economic Characteristicsmentioning
confidence: 97%
“…In the central zone of Tigray, Gebrekidan et al (2012) also indicated that the proportion of male household heads was higher than that of female heads. This indicates that females are less dependent on urban dairy production than males, so attention must be given to the females participation in smallholder dairy farming for work, employment, and income generation.…”
Section: Socio-economic Characteristicsmentioning
confidence: 97%